The development of ventricular fibrillation as a complication of pericardiectomy in 16 dogs. Issue 4 (7th March 2022) - Raleigh, Joseph S.; Mayhew, Philipp D.; Visser, Lance C.; Milovancev, Milan; Kuntz, Charles A.; Formaggini, Luca; Chiu, Hsien‐Chieh; Skinner, Owen T.; Naiman, Jaron H.; Oblak, Michelle L.; McAnulty, Jonathan F.; Hoffman, Christopher L.; et al.
Abstract: Objective: To describe the clinical characteristics, perioperative protocols, and outcomes in dogs diagnosed with ventricular fibrillation (VF) while undergoing pericardiectomy. Study design: Retrospective, multi‐institutional study. Animals: Sixteen client‐owned dogs. Methods: Cases were accrued through a listserve request posted to 3 subspecialty veterinary societies. Dogs were included if they developed VF during a pericardiectomy performed through an open or thoracoscopic approach. Data collected included signalment, history and physical examination, surgical approach, histopathology, treatment, and outcome. Results: Indications for pericardiectomy included idiopathic chylothorax ( n = 7), neoplasia (4), idiopathic pericardial effusion (4), and foreign body granuloma (1). Surgical approaches included thoracoscopy (12), intercostal thoracotomy (3) and median sternotomy (1). Electrosurgical devices were used to complete at least part of the pericardiectomy in 15 of 16 dogs. Ventricular fibrillation appeared to be initiated during electrosurgical use in 8/15 dogs. However, in 5/15 dogs it was not obviously associated with electrosurgical use. In 3/16 dogs the timing of initiation of VF was unclear. In 7/16 dogs, cardiac arrhythmias were noted prior to the development of VF. Fourteen of 16 dogs died from intraoperative VF. Conclusion: In most dogs ventricular fibrillation was a fatal complication of pericardiectomy. Ventricular fibrillation might be associated with the use of electrosurgical devices and cardiac manipulation during pericardiectomy although a causal link could not be established from the data in this study. Clinical significance: Surgeons must be aware of the risk of VF during pericardial surgery. Electrosurgery might need to be used judiciously during pericardiectomy, particularly in dogs exhibiting cardiac arrythmias.